Sistem Pendukung Keputusan Seleksi Pemilihan Kepala Bagian Perum Damri Surabaya - Maslihah; Rafdani Mufid (Informatics Engineering Department-UWKS, 2017)
The process of appointing candidates for head of the department at Perum DAMRI Surabaya still use the manual method. With the development of today's technology Perum DAMRI Surabaya needs a new method so that it can provide recommendations in choosing the head section. Based on the existing problems then the authors take the title